Twenty-year changes of adolescent mental health and substance use : a Finnish population-based time-trend study - Mishina, Kaisa; Heinonen, Emmi; Lempinen, Lotta; Sourander, Andre (Springer Nature, 2025)
This time-trend study assesses changes in mental health and substance use among Finnish adolescents from 1998 to 2018. Representative samples of adolescents (N = 6,600) aged 13-16 years participated in school-based, almost identical cross-sectional studies in 1998 (n = 1,446), 2008 (n = 2,009), 2014 (n = 1,800) and 2018 (n = 1,345), respectively. The Strengths and Difficulties Questionnaire was used to assess mental health. When comparing mental health in the clinical range between 1998 and 2018, the main finding was the significant increase of emotional symptoms among females. The percentage of females in the clinical range increased from 17.5 to 30.1% during the twenty-year period. When psychopathology measures were analyzed as continuous variables, the finding of increased emotional problems was confirmed. The study clearly illustrates a linear trend, with a consistent increase in emotional problems among females and decrease in substance use among both genders. An alarming finding of steady increase of self-reported emotional problems indicates the importance of early detection and evidence-based interventions for adolescent with anxiety and depression to prevent adversities associated with these disorders.